A first-approximation simple dynamic growth model for forest teak plantations in Gujarat state of India. Issue 1 (2nd January 2018) - Tewari, Vindhya Prasad; Singh, Bilas
Abstract : Tectona grandis (teak) is one of the most important tropical timber species occurring naturally in India. In India, teak is the single most important commercial timber species. Scientifically sound growth models, based on advanced modelling techniques, are often not available, although they are necessary for the successful management of teak stands in the country. Long-term forest planning requires mathematical models. In this paper, an attempt is made to develop a dynamic growth model based on the limited data, consisting of three annual measurements, collected from 15 teak sample plots in Gujarat state of India. A biologically consistent whole-stand growth model is presented, which uses the state-space approach for modelling rates of change of dominant height, stand density and stand basal area. A simple model containing few free parameters performed well and is particularly well suited to situations where available data are scarce.